Strategi Pendamping Umroh Dalam Menghadapi Perilaku Jama’ah Di PT. Brahmana Muda Sentosa - M Abrori Mulya Abror; Anang Walian Anang (Social Science and Contemporary Issues Journal, 2023)
This thesis is entitled "Umrah Companion Strategy in Dealing with Congregation Behavior at Pt. Young Brahmin Sentosa”. This research was motivated by the lack of knowledge of the pilgrims about the Hajj pilgrimage and the diverse behavior of the pilgrims who were considered to be still inefficient in providing guidance at Pt. Young Brahmin Saentosa. To follow up on this problem the author went directly into the field to find accurate data by interviewing the head of Pt. Brahmin Muda Sentosa and the congregation at Pt. as a resource person. This is done to anticipate that there will be pilgrims who are lagging behind in their understanding of the Hajj and Umrah pilgrimages. This research uses a type of field research, namely research carried out by coming directly to the place where the problem occurs. The technique used in this research is a survey technique by distributing questionnaires to respondents, this is to obtain valid data and facts in the field or research location. This research uses quantitative methods which emphasize numerical data (numbers) which are processed using statistical methods. The primary data in this research refers directly to resource interviews and questionnaire results from respondents, while the secondary data is obtained from books, articles related to research and archival documentation as well as activities from the Pt. Brahmin Sentosa. The results of this research show that the strategy for assisting the Umrah pilgrims at Pt. Brahmana Sentosa, namely by giving ID cards to the congregation one by one, this is done to make it easy to find pilgrims who are separated from the group. The ID card is worn around the neck of each congregation and on the back of the ID card is written Muthoif's name, hotel, cellphone number and the name of the Tour Leader so that it is easy to ask people there for help. The supporting factors for mentoring at Pt. Brahmin Sentosa, as the leader who guides, must prepare loudspeakers and prepare a travel flag.